Association of Sleep Apnea with Resistant Hypertension and Cardiovascular Morbidity in Obese Adults. A Comparative Clinical Study - Aamir Siddique, Shaoib Ahmed Zia, Muhammad Zahid Ali Raza, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obstructive sleep apnea (OSA) and resistant hypertension are interrelated conditions that frequently coexist in obese individuals, markedly increasing the risk of cardiovascular complications. Although their association is well recognized, the extent and severity of cardiovascular morbidity attributable to their coexistence remain inadequately explored in clinical practice. Objective: To evaluate the association between OSA and resistant hypertension in obese adults and to assess the impact of OSA severity on cardiovascular outcomes. Methodology: This comparative clinical study included 200 obese hypertensive patients aged 30–65 years, comprising both males and females. Participants were categorized into two groups: controlled hypertension (n = 104) and resistant hypertension (n = 96). All subjects underwent overnight polysomnography to determine the severity of OSA. Comprehensive biochemical profiling was performed, including metabolic and inflammatory biomarkers such as hs-CRP, IL-6, TNF-α, and serum aldosterone. Cardiovascular evaluation included echocardiography and documentation of clinical history of myocardial infarction, stroke, and heart failure. Results: OSA was significantly more prevalent in the resistant hypertension group (92.7%) compared to the controlled hypertension group (56.7%) (p < 0.001). Severe OSA was disproportionately higher among patients with resistant hypertension. Inflammatory markers and serum aldosterone levels were significantly elevated in the resistant group (p < 0.001). Cardiovascular complications, including left ventricular hypertrophy, diastolic dysfunction, and myocardial infarction, were also markedly more common in patients with resistant hypertension and concurrent OSA. Conclusion: This study establishes a strong association between OSA and resistant hypertension, highlighting the substantial contribution of OSA to cardiovascular morbidity in obese individuals. Early identification and management of sleep-disordered breathing in hypertensive patients may improve therapeutic outcomes and mitigate long-term cardiovascular risk. Keywords: Resistant hypertension, Obesity, Cardiovascular morbidity, Inflammatory biomarkers, Left ventricular hypertrophy, Diastolic dysfunction, Polysomnography.